KOLAM TOWN, DELI SERDANG DISTRICT EMPOWERMENT OF SMALL MEDIUM ENTERPRISES (UKM) - Muya Syaroh Iwanda Lubis; Muhammad Sabili (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2022)
ABSTRACT This activity aims to improve the quality of financial accounting, the quality of packaging and the Small and Medium Enterprises (UKM) trademarks in Pond Village. The problems faced by Partners here are; (1) financial management can be said to be not maximal where only used paper is used, the calculations are only digging holes and closing holes (there is no calculation of capital and profits, it is not uncommon for capital and profits to be used for other purposes) and (2) packaging of banana chips using kilo sugar plastic so that the packaging often leaks, tears, and is not attractive and does not yet have a trademark. The solutions offered here, Partners are given training, education, mentoring, outreach, and submission of Appropriate Technology (TTG) regarding the problems faced by Partners. The method of implementing the service program will be carried out in an approach, namely obtaining initial information until the activity process is carried out by direct communication or through intensive communication tools with Partners, so that the implementation of activities can be carried out in a guided manner, with the main objective to improve the welfare of Partners in managing Small and Medium Enterprises (SME). UKM), namely banana chips business . manner, with the main objective to improve the welfare of Partners in managing Small and Medium Enterprises (SME). UKM), namely banana chips business.Keywords: Empowerment Of Small Medium Enterprises (UKM), Kolam Town